DEVELOPING PRODUCT IDENTITY AND DIGITAL MARKETING FOR SUSTAINABILITY: A CASE STUDY OF ISAAN LANNA FARMERS IN CHIANG RAI PROVINCE - นิลดำ กรกนก; โตธนายานนท์ กฤศ; นิลดำ เสริมศิริ (Thai Interdisciplinary and Sustainability Review, 2025)
This article presents a qualitative study investigating the development of product identity and digital marketing strategies to promote sustainability among Isaan Lanna farmers in Chiang Rai province. The study focuses on Chiang Saen district, an area characterized by a fusion of Isaan and Lanna cultures. The research methodology includes participatory research and action research. The findings suggest that product identity development should emphasize local culture and natural elements. Digital marketing communication strategies should prioritize the use of social media and creating shared experiences with consumers. Additionally, developing community marketing communicators with storytelling skills and appropriate media usage is a key factor for successful and sustainable marketing communication. This study has implications for promoting sustainable community product marketing and generating income for local farmers.